2019
DOI: 10.1177/1035304619831245
|View full text |Cite
|
Sign up to set email alerts
|

Application of job security laws, workers’ bargaining power and employment outcomes in India

Abstract: This article empirically investigates two propositions normally advanced to explain employment stagnation in the organised sector of the Indian labour market namely, rigid labour laws regulating the 'hiring and firing' of workers (along with factory closures) and militant trade union activity boosting workers' bargaining power. It is claimed that labour laws arrest employment creation by making the labour adjustment process difficult. Additionally, it is claimed that workers' increased bargaining power raises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Our empirical analysis showed that the reforms had an unintended consequence of the decline in labor use. The implications regarding employment are similar to those presented by Roy, Dubey, and Ramaiah (2020), Deakin and Haldar (2015), Roychowdhury (2019a), Chatterjee and Kanbur (2015), D'Souza (2010), Kapoor (2014), Chandru(2014) in the sense that higher flexibility is associated with weaker employment growth. Also, worryingly, the increased flexibility resulted in the reduction in the directly employed workers.…”
Section: Discussionsupporting
confidence: 78%
“…Our empirical analysis showed that the reforms had an unintended consequence of the decline in labor use. The implications regarding employment are similar to those presented by Roy, Dubey, and Ramaiah (2020), Deakin and Haldar (2015), Roychowdhury (2019a), Chatterjee and Kanbur (2015), D'Souza (2010), Kapoor (2014), Chandru(2014) in the sense that higher flexibility is associated with weaker employment growth. Also, worryingly, the increased flexibility resulted in the reduction in the directly employed workers.…”
Section: Discussionsupporting
confidence: 78%
“…Aggregate union membership in India appears to have risen from around 35 million workers in 2008 to around 100 million workers in 2013 (Menon, 2013). This is a rather intriguing phenomenon and runs counter to the general consensus in the literature about the adverse impact of nearly three decades of economic reforms in India on the fortunes of Indian trade unions (Bhattacherjee, 2001;Roychowdhury, 2019;Sharma et al, 2014). Similar trends in union membership growth have been reported in some other countries of the Global South.…”
Section: Introductionmentioning
confidence: 75%
“…Higher bargaining power of the laborers is likely to secure paid leaves during the lockdown, which would reduce the severity of the pandemic. We take the state's percentage share of industrial disputes in India in 2016 to capture the bargaining power of the workers (Roychowdhury, 2019). The income transfer made by the state governments to the vulnerable workers during the lockdown, as illustrated in Appendix Table A1, increases the financial resilience (Lal, 2018), which secures the health of the workers during the pandemic.…”
Section: Methodsmentioning
confidence: 99%